Effects of soil compaction and mechanical damage at harvest on growth and biomass production of short rotation coppice willow - Souch, C. A.; Martin, Peter J.; Stephens, William; Spoor, G. (Springer Science Business Media, 2004)
The effects of soil compaction and mechanical damage to stools at harvesting on the growth and biomass production of short rotation coppice (SRC) of willow (Salix viminalis L.) were monitored on clay loam (CL) and sandy loam (SL) soils. Moderate compaction, more typical of current harvesting situations did not reduce biomass yields significantly. Even heavy compaction only reduced stem biomass production by about 12% overall; effects were statistically significant only in the first year of the experiment on sandy loam. Heavy compaction increased soil strength and bulk density down to 0.4 m depth and reduced soil available water and root growth locally. Soil loosening treatments designed to alleviate the effects of heavy compaction did not markedly improve the growth of willow on compacted plots. Hence the focus fell on harvesting. Extensive mechanical damage to stools caused a 9% and 21% reduction in stem dry mass on the clay loam and sandy loam soils as a result of fewer stems being produced. The particularly severe effect on the sandy loam soil probably resulted from a combination of dry conditions in the year of treatment, root damage and soil compaction under stools and might have been aggravated by the young age of the plants (1 year) at the time of treatment.